ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VII PADA MATERI BILANGAN BULAT - Fajri Wulan Dini; Sri Yunita Ningsih (Ensiklopedia Research and Community Service Review, 2026)
This study aims to determine the mathematical communication skills of students in integer material in grade VII of SMP Negeri 1 Pasir Penyu. The method used is a descriptive qualitative method in the form of research in the form of a case study. The sample of this study is 30 students. The results of the average score pattern from indicator 1 are high ability level, which is 3, medium is 2.5, and low is 1.67 with a total average of 2.33. From indicator 2, the level of ability is high, which is 3.8, medium is 2.8, and low is 1.23 with a total average of 2.47. From the indicators 3, the level of ability is high, which is 2.8, medium is 1.89, and low is 1.87 with a total average of 2.03. Of the 4 indicators, the level of ability is high, which is 3.8, medium is 2.25 and low is 1.78 with a total average of 2.37. In general, it can be concluded that the mathematical communication skills of students are high, which is 5 people or 16.67%, while 16 people or 53.33%, and low, which is 9 people or 30%.Keywords: Mathematical Communication, Learners.